Firefly Cove [large type] - Bunn, T. Davis, 1952- (Bunn, T. Davis, 1952- Miramar Bay, 2018)
"Set in the small California coastal town of Miramar Bay, a dying young man, Lucas Quarterfield, must say goodbye to the woman he loves. Almost fifty years later through unusual circumstances he receives as second chance to be near the only woman he ever wanted"--